À la carte - Ladies & Gents; Hannikainen, Markku; Andersin, Tobias; Hakkarainen, Veikko, 1941-; Katrama, Jorma, 1936-2022; Lae, Kalle; Leander, Pekka; Maarala, Janne; Mikkeli, Jorma; Pinomaa, Simo; Renko, Markku (trumpetisti); Saikkonen, Merja; et al. ([Suomi] : Pekka Leander, 2017)
11 kappaletta.
All the way ; Sunrise, sunset ; Iberique peninsulaire ; The thrill is gone ; Valse de belleville ; Some of these days ; Brasiliana ; But beautiful ; Good old days ; Blood count ; Over the rainbow.
Pekka Leander (tuottaja).
Ladies & Gents (yhtye): Tobias Andersin (lauluääni), Merja Saikkonen (lauluääni), Markku Renko (trumpetti), Pekka Leander (pasuuna), Simo Pinomaa (sopraanosaksofoni, tenorisaksofoni), Veikko Hakkarainen (piano), Jorma Katrama (sähköbasso), Jorma Mikkeli (rummut), Jan Vaaka (lyömäsoittimet), Janne Maarala (piano 5, 10), Kalle Lae (kitara 1), The Soul Strings (yhtye), Markku Hannikainen (johtaja 1, 8, 11).
Keywords: jazz; soul; viihdemusiikki